The Principles underlying the Awarding of the Concession Contract for Public Property Assets - Negrut, Vasilica (Acta Universitatis Danubius. Juridica, 2023)
The paper addresses a current problem not only for legal research, but also for practitioners. Thus, we resume a subject on which other authors have analyzed, namely the concession contract, thus highlighting, based on the analysis and comparison, certain particularities of the principles that underlie the awarding of the concession contract of public property assets. The principles established in the Administrative Code, namely transparency, equal treatment, proportionality, non-discrimination, and free competition are intended to ensure objectivity and efficiency in this procedure.